(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Soilsalinityisaglobalproblem.Soilsalinizationbadlyaffects agriculturallands.Itisnegativelyaffectingplantgrowth,cropyieldsduetoover-irrigation,monocultureofsugarcane, using polluted water of the river leading the further land degradation. It is also amajorconcerninthelowerMula-MuthaRiverbasininwesternMaharashtra,wheretheclimateis arid and semi-arid. The objectives of this study were to estimate the salt affected area anddelineatemappingvariationsinthestudyareausingRSdata.Traditionalsoilsalinityassessments have been done by collecting soil samples and laboratory analyzing of collectedsamples for determining soil pH andelectroconductivity (EC).Geographical InformaticsSystems (GIS) and Remote Sensing (RS) technologies are used to provide more efficient,economic,andrapidtoolsandtechniquesforsoilsalinityassessmentandsoilsalinitymapping.Using Landsat-8 OLI/TIRS satellite images, Soil Adjusted Vegetation Index (SAVI) andNormalizedDifferenceSalinityIndex(NDSI)arestudiedforfindingoutthesoilsalineareaofthe basin. It is found that more than 65% of the soil in the study area is moderate to highlysaline as per SAVI while more than 50% area is covered by moderately to highly saline areasaccording to NDSI. The results support that geoinformatics techniques using RS data andtechnologies constitute an effective tool for detecting soil salinity by modeling and mappingthe spatial distribution of saline soils. Use of gypsum, no use of polluted river water foragriculture,andavoidofover-irrigationaresuggestedtoreducethesoilsalinityprobleminthelower Mula-Mutha River basin. Similar methodology can be used for the evaluation andmappingofsoilsalinity-affectedareas in thearidand semi-aridparts of India.